Domestic wastewater treatment by a constructed wetland system planted with rice - Suwasa Kantawanichkul (2018)
The experiments were conducted in four concrete laboratory scale free water surface constructed wetland units 1 m wide, 1.5 m long and 0.8 m deep. Paddy field soil was added to a depth of 0.4 m and rice seedlings (Oryza sativa L.) were transplanted into the units at a density of 25 plants/m 2. Domestic wastewater collected from Chiang Mai University was applied into each unit via two different modes to evaluate suitable conditions for wastewater treatment and rice yield. In the first experiment, the wastewater was fed intermittently (7 h/day) with a hydraulic loading rate of 2, 4, 6 and 8 cm/day. The maximum removal efficiencies for chemical oxygen demand, biological oxygen demand, total kjedahl nitrogen and suspended solids were only 49.1, 58.7, 64.0 and 59.4%, respectively, due to the short hydraulic retention time for the biodegradation of organic substances. In the second experiment, the wastewater in each unit was inundated to a depth of 15 cm for 10, 15, 20 and 25 days in each unit and then drained and re-flooded. Removal efficiencies of chemical oxygen demand, biological oxygen demand, total kjedahl nitrogen and suspended solids were greater than in the first experiment especially at the 25 day retention time and except for suspended solids met the Thai national effluent standard. The study revealed that apart from wastewater treatment, wastewater can replace natural water to grow rice in the dry season or throughout the year. Moreover, nutrients in wastewater can be a substitute for chemical fertilizers. Rice grain production was 4,700 kg/ha and only 6% less than the production from the conventional paddy field. © IWA Publishing 2011.